Service delivery models for enhancing linkage to and retention in HIV care services for adolescent girls and young women and adolescent boys and young men: a protocol for an overview of systematic reviews. Issue 9 (19th September 2022) - Jonas, Kim; Zani, Babalwa; Ramraj, Trisha; Chirinda, Witness; Jama, Ngcwalisa; Basera, Wisdom; McClinton Appollis, Tracy; Pass, Desiree; Govindasamy, Darshini; Mukumbang, Ferdinand C; Mathews, Catherine; Nicol, Edward
Abstract : Introduction: Recent advances in the HIV care continuum have shown that an individual diagnosed with HIV should be initiated on antiretroviral therapy as soon as possible regardless of the CD4 count levels and retained in HIV care services. Studies have reported large losses in the HIV continuum of care, before and after the era of universal test and treat. Several systematic reviews have reported on the strategies for improving linkage to and retention in HIV treatment and care. The purpose of this overview of systematic reviews is to identify HIV care interventions or service delivery models (SDMs) and synthesise evidence on the effects of these to link adolescent girls and young women (AGYW) and adolescent boys and young men (ABYM) to care and retain them in care. We also aim to highlight gaps in the evidence on interventions and SDMs to improve linkage and retention in HIV care of AGYW and ABYM. Methods and analysis: An electronic search of four online databases: PubMed, Cochrane Database of Systematic Reviews, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Web of Science will be performed to identify systematic reviews on the effects of linkage to and retention in HIV care interventions or SDMs for AGYW aged 15–24 years and ABYM aged 15–35 years. Our findings on the effects of interventions and SDMs will be interpreted considering the intervention and or SDMs' effectiveness by the time period, setting and population of interest. Two or more authors will independently screen articles for inclusion using a priori criteria. Ethics and dissemination: Ethics approval is not required for this study as only published secondary data will be used. Our findings will be disseminated through peer-reviewed publication, conference abstracts and through presentations to stakeholders and other community fora. The findings from this overview of systematic reviews will inform mixed-methods operations research on HIV intervention programming and delivery of HIV care services for AGYW and ABYM in South Africa. PROSPERO registration number: CRD42020177933.